PTH-151 Are the current management strategies for T1/T2 n0 oesophageal cancer optimal?. (22nd June 2015) - Evans, R; Evans, JP; Kirby, G; Curran, F; Cheruvu, CVN
Abstract : Introduction: Stage directed therapy based on the imaging modalities remains the cornerstone of oesophageal cancer management. EUS and CT imaging are the commonly used modalities to stage patients with oesophageal cancer, with sensitivity of 90% and 70% for T staging respectively; EUS provides up to 70% accuracy in N stage. Neoadjuvant chemotherapy is recognised to reduce 3-yr mortality in the patients with stage II/III oesophageal cancers. Due to the limitations in the preop staging modalities, a cohort of patients with preop T1/2 risk being under staged and have surgery as the index treatment option, who may have otherwise benefited from neoadjuvant therapy. We aim to assess the number of patients who had stage migration following oesophagectomy having being staged as T1/T2 and N0 preoperatively. Method: This study includes a cohort of consecutive patients who had oesophagectomy between 2008–2014. EUS, CT and PET scanning of all patients' results were reviewed, with emphasis on those with T1/T2 N0 disease. Data on patients with T1/T2 N0 disease who went straight to surgery was analysed. The primary end points include staging migration on post-operative histology, perioperative mortality, morbidity and survival. Results: In the 6-yr study period, 330 oesophagectomies were performed of which 62 patients had preoperative T1/2 N0 disease (18.7%); 20 patients with T1 N0 and 42 patients with T2 N0. The median age was 64 years (range 46–81) and 46 (74.1%) of the patients were male. Amongst these, 56 patients had Ivor-Lewis oesophagectomies, MIOs in 3 and 3 had a trans-hiatal operations with curative intent. Median length of stay was 13 days (range 7–97) whilst minor and major complications occurred in 43.5% (n = 27). Postoperative deaths occurred in 3 patients (4.8%) during their index admission as a result of (anastamotic leak (1), bowel ischaemia (1) and stroke (1)). Amongst the 62 with preoperative T1/T2 disease, postoperative stage migration was found in 25 (40.3%) patients who were upstaged to pT3 disease (13 patients). Nodal disease was found in 20 patients while 8 patients had R1 resections. A cohort of these patients had adjuvant therapy. In our cohort, 6 died (mean 795 days, range 181–1545). The remaining two patients had no recurrence at 455 and 804 days post surgery. In total, 14 patients received adjuvant treatment; 9 patients developed recurrence (median 557 days, range 303–1336) and 13 patients died during their follow up (median 400 days post op, range 8–1545). To date, 41 patients remain under follow up with median survival of 879 day (range 160–2363 days). Conclusion: This study concludes that there were a significant number of people who were under staged and were not offered potentially curative treatment options. Disclosure of interest: None Declared.